Problems and Prospects of Rural Marketing in Bangladesh - Hossain, Md. Sabbir; Hossain, Md. Motahar; Moshiuddullah, A.B.M; Hasan, Md. Mahmudul (Business and Economic Research, 2025)
The research aimed to examine the prospects of Bangladesh's rural marketplaces and identify the issues these markets are currently dealing with. Both primary and secondary data have been used for the study. Primary data has been collected using Google Forms and analysed to achieve the research goal. The idea of rural marketing is more expansive than the idea of agricultural marketing. It encompasses the movement of commodities into and out of the country's rural areas, as well as the sale of various products produced by non-agricultural employees between rural and urban regions. Marketers have recently realized the potential of rural marketing, an emerging concept with unexplored potential as a component of any economy. This paper tries to give a concise overview of the research on marketing for remote areas and provides suggestions aimed at improving the performance of rural markets.